A rare cause of embolism in the popliteal artery of an adolescent: ruptured cardiac hydatid cyst - Ozturk, Mehmet; Sigirci, Ahmet; Dagli, Adile Ferda (Turkish Soc Cardiology, 2015)
[Abstract Not Available]